2011
DOI: 10.1063/1.3665682
|View full text |Cite
|
Sign up to set email alerts
|

Metal nanoparticles in a photovoltaic cell: Effect of metallic loss

Abstract: We examined numerically the contribution of contrasting characteristics of metal nanoparticles, strong polarization and metallic loss, to the total efficiency of photovoltaic cells. A layer of nanoparticle array was chosen as a model. We found that depending on the location of the layer in the cell, the metallic loss offsets the enhanced photoabsorption due to the strong near field. A general procedure to reduce a nanoparticle layer into a sheet of effective continuous medium is presented, which greatly facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…For the devices with Au nanorods positioned at the QD/ZnO interface (Figure (c)), the average J sc is 0.35 mA/cm 2 , a little lower than that of the control devices. This observation is consistent with previous studies ,, and is likely due to exciton quenching and trap-assisted charge recombination at the Au nanorod surface. This argument is further supported with the transient photovoltage measurement of the photodiodes (Figure S2 in the Supporting Information), where the QD/Au nanorod/ZnO structure exhibits much faster transient photovoltage decay than the other device structures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the devices with Au nanorods positioned at the QD/ZnO interface (Figure (c)), the average J sc is 0.35 mA/cm 2 , a little lower than that of the control devices. This observation is consistent with previous studies ,, and is likely due to exciton quenching and trap-assisted charge recombination at the Au nanorod surface. This argument is further supported with the transient photovoltage measurement of the photodiodes (Figure S2 in the Supporting Information), where the QD/Au nanorod/ZnO structure exhibits much faster transient photovoltage decay than the other device structures.…”
Section: Resultsmentioning
confidence: 99%
“…Early studies showed that directly blending metal NPs into the photoactive layer of a device leads to little or no photocurrent improvement even though the plasmon-enhanced optical absorption is significant. This is mainly due to exciton quenching and trap-assisted charge recombination at the surface of the metal NPs. ,, Recent research demonstrated alternative approaches such as doping Au-TiO 2 core–shell nanoparticles into the porous TiO 2 layer of dye-sensitized solar cells , and embedding self-assembled Au nanopyramid arrays into the poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate) (PEDOT:PSS) buffer layer of organic solar cells . These studies achieved up to 50% increment of the short-circuit current density ( J sc ) thanks to the surface passivation and good dispersion of the Au NPs in the buffer layers.…”
mentioning
confidence: 99%
“…Polymer-metal nanocomposites and interfaces play an important role in many areas of technology and research (Walter, 2006;Akamatsu & Deki, 1997;Kharkwal et al, 2011). This includes, for example, devices for sensing applications (Bauer et al, 2003), catalysis (Lee et al, 2013;Sugunan et al, 2010;Li et al, 2012), organic electronics (Mentovich et al, 2010;Watanabe & Miyano, 2011), plasmonics (Babonneau et al, 2011(Babonneau et al, , 2012, organic photovoltaics (Perlich et al, 2009) and future storage technology (Martinez-Tong et al, 2013). It is well known that many of these devices rely on metal nanoparticles owing to their size-dependent and adjustable physical and chemical properties (Yeh et al, 2012;Jin, 2010;Kim et al, 2009;Xu et al, 2010;Zheng et al, 2012;Romo-Herrera et al, 2011;Wu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…and experimentally observed that in these configurations the effect of the MNPs is similar to that of an anti-reflection coating (ARC) or a rear mirror layer. So, a better choice is just to use such conventional layers instead of the MNPs, since the MNPs always exhibit more dissipation (light absorption) at energies away from their plasmonic frequency [90,91]. In other words, the easiness of the application of MNPs on the top or bottom surface of the cell does not make a case for their use in this configuration.…”
Section: Introductionmentioning
confidence: 99%